Serum klotho and FGF23 Levels in Patients with Schizophrenia - Kilicaslan, Asli Kazgan; Yildiz, Sevler; Emir, Burcu Sirlier; Kilic, Faruk; Atmaca, Murad (Aves, 2022)
Background: The aim of this study is to compare the serum levels of Klotho and fibroblast growth factor 23 in patients with schizophrenia, in whom etiopathogenesis inflammation plays an important role, with those of healthy control subjects and to investigate a possible correlation between these levels. Methods: Forty male patients with schizophrenia and 40 healthy mate control subjects who were followed up and/or treated at the High-Security Forensic Psychiatry Clinic participated in the study. Sociodemographic data form, the Positive and Negative Syndrome Scale, and the Clinical Global Impression Scale were collected from all subjects, and participants' fibroblast growth factor 23 and Klotho serum levels were measured by the enzyme-linked immunosorbent assay method. Results: The serum levels of Klotho and fibroblast growth factor 23 were significantly higher in schizophrenia patients than in healthy controls (P = .048 and P = .010, respectively). A significant positive correlation was observed between serum levels of Klotho and fibroblast growth factor 23 in subjects (r=0.816; P < .001). Conclusion: Our study is the first to show significantly higher combined serum levels of fibroblast growth factor 23 and Klotho in patients with schizophrenia. The Klotho/fibroblast growth factor 23 pathway may play a rote in the pathogenesis of schizophrenia. The involvement of Klotho and fibroblast growth factor 23 in inflammatory processes has the potential to provide alternative approaches to elucidate the etiopathogenesis and treatment of schizophrenia.
Keywords: Fibroblast growth factor 23; inflammation; klotho; schizophrenia; serum